Radical Truce-Smiles reactions on an isoxazole template: Scope and limitations. Issue 16 (19th April 2019) - Rashid, Srood O.; Almadhhi, Sultan S.; Berrisford, David J.; Raftery, James; Vitorica-Yrezabal, Inigo; Whitehead, George; Quayle, Peter
Abstract: The use of TiCl3 -HCl as promotor in the radical Truce-Smiles reactions of 2-(((3, 5-dimethylisoxazol-4-yl)sulfonyl)oxy)benzenediazonium salts has been investigated in detail. During these reactions the desired Truce-Smiles rearrangement ( via an ipso -substitution reaction) is accompanied by the formation of a number of by-products including dihydrobenzo[5, 6][1, 2]oxathiino[3, 4- d ]isoxazole 4, 4-dioxides, dioxidobenzo[e][1, 2]oxathiin-3-yl)ethan-1-ones, anilines and chloroaromatics. Replacing TiCl3 -HCl by Cu(NO3 )2 -Cu2 O as reductant in these reactions was found to afford broadly comparable product distributions. Competition and radical clock experiments also provide an indication of the relative susceptibility of the isoxazole nucleus towards attack by aryl radicals. Graphical abstract: Image 1